CLINICAL SPECTRUM OF DENGUE FEVER AND DENGUE HEMORRHAGIC FEVER AMONG CHILDREN AT SANGLAH HOSPITAL DENPASAR: A THREE-YEAR RETROSPECTIVE STUDY - Kanya Wati, Dyah; Arhana, BNP (Medicina, 2012)
Spondilitis tuberculosis merupakan fokus sekunder infeksi tuberculosis yang mengenai tulang belakang. Keterlibatan tulang belakang akan dapat memperberat morbiditas karena adanya potensi defsit neurologis dan deformitas yang permanent. Diagnosis ditegakkan berdasarkan klinis, laboratories, imaging, bakteriologis dan histopathologis. Sampai saat ini belum ada therapi definitif yang baku. Masih ada kontroversi antara terapi konservative dengan pembedahan. Telah dikembangkan metode total treatment yang merupakan gabungan terapi konservatif dan tindakan operatif berdasarkan identifikasi masalah yang dihadapi masing ? masing penderita.Therapi pembedahan dapat berupa radikal atau middle path, Study of spectrum of dengue fever and dengue hemorrhagic fever on children at Sanglah General Hospital Denpasar was done in 2005.Data were collected from medical records. Subject of this study were patients of dengue fever (DF) and dengue hemorrhagic fever (DHF) who were admitted to the pediatric department of Sanglah hospital from 1 January 2002 until 31 December 2004. There were 837 patients diagnosed, 582 were eligible to inclusion; 303 (52.1%) males and 279 (47.9%) females. Most of them were diagnosed with DF 417 (71.6%), DHF 95 (16.3%), and DHF with shock 70 (12.0%). Five patients (0.8%) died because of DHF with shock in three years and 4 of them were females. Patients mostly came on the fourth day 337 (57.9%). Vomiting 283 (48.6%), 66 (11.3%) was the major symptom of patients with DF and DHF respectively, hepatomegaly 61(10.5%) and abdominal pain 59 (10.1%) were major symptoms of DHF with shock. Hemorrhagic manifestation was petechiae; 310 (53.3%) of DF, 63 (10.8%) of DHF, 42 (7.2%) of DHF with shock. From laboratories result, leukopenia and thrombocytopenia were major findings. The number of patients with DF and DHF reached the peak level in March in three years. The conclusion of this study is DF AND DHF mostly occur in males. Hepatomegali, abdominal pain and vomiting are major clinical symptoms. Petechiae is the major hemorrhagic manifestation. Leukopenia and trombositopenia are majority laboratories findings in patients with DF and DHF. Peak level of patients is in March in three years.
Keywords: dengue fever, dengue hemorrhagic fever, spectrum, children